Inspiration to pursue study : youth from rural area / Razzidin Robert and Ivy Sendralisa H.James Arab - Robert, Razzidin; H.James Arab, Ivy Sendralisa (2018)
This paper focuses on reviewing literature on the inspiration in education youth from rural area. Education plays important things to the society especially to the people at rural area. The study was examined to identify what makes youth from rural area inspired to pursue study and to determine how inspiration from educator, parent and education system can encourage the youth from rural area to pursue studies. A random sample of 100 people in Kg. Kemburongoh Ranau was a respondent to this study to achieve the objective in this study. The information was gain from primary data, secondary data and also used the mixed method which was the quantitative and qualitative data. Not surprisingly, the people was perform studies by three variable which is parents, teacher, also the education system. By looking at the current education system, government provides education plan which differ on the increasing of student who complete their study. Besides, the research is being conduct at Ranau to answer the researcher questionnaire. Researchers have identified that Teacher is the most significant that contribute to inspire in education while for the two factor which is parents and education system was not significant. In addition, the educator was very important to make the student inspired to pursue study. However, Malaysian government itself need to improve the quality of skills among educator to keep the rate of student to pursue study keep increased.